Implementation and evaluation of the 3 Wishes Project in safety-net hospitals: Protocol for a hybrid effectiveness-implementation study - Thanh H. Neville; Anne Walling; Neil S. Wenger; Brian S. Mittman; Chi-hong Tseng; Dong Chang; Deborah Cook; Carolyn Jennifer Marentes Ruiz; Hope Cassano; Emily Beers; Rucha Gadgil; Nader Kamangar; et al. (PLoS ONE, 2025)
Background Palliative care interventions in the intensive care unit have been shown to improve communication and the quality of death and dying. However, few interventions have been implemented in safety-net hospitals (SNHs), which provide healthcare to low income and uninsured patients. The 3 Wishes Project (3WP) is a low-cost intervention that aims to enhance compassionate end-of-life (EOL) experiences by empowering the clinical team to elicit and fulfill small wishes for patients who are dying in the ICU. Objective To implement and evaluate the 3WP in three SNHs in Los Angeles. Methods We conduct a pragmatic cluster-randomized stepped wedge type 2 hybrid effectiveness-implementation study to implement and evaluate the effect of the 3WP (compared to usual care) on quality of EOL ICU care, bereaved families’ psychological symptoms, and clinician burnout. Prior to implementation, interviews with stakeholders from each hospital will refine the implementation strategy. Starting 6–10 months prior to 3WP implementation at each site and continuing throughout the study, we will survey bereaved families once 3 months after each patient’s death. Surveys will query: EOL care, anxiety, depression, and post-traumatic stress disorder (PTSD). Each SNH ICU starts the 3WP at a randomly assigned time that is staggered by 2 months. Nurses are surveyed on burnout before implementation, 6 months, and 12 months after 3WP implementation. Semi-structured interviews are conducted with 10–12 family members per SNH who received 3WP and 10–12 nurses per SNH a year after implementation. We will use the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework to guide a mixed-methods evaluation of the 3WP implementation in SNHs. Conclusion We hypothesize that it will be feasible to adapt and implement the 3WP in SNHs. We will evaluate how the 3WP improves EOL care in this setting and provide valuable insight regarding the adaptations necessary to tailor palliative care interventions for SNH ICUs. Trial registration ClinicalTrials.gov NCT06277310.